Obesity can predict and promote systemic inflammation in healthy adults. (15th July 2016) - Ellulu, Mohammed S.; Khaza'ai, Huzwah; Rahmat, Asmah; Patimah, Ismail; Abed, Yehia
Abstract: Background: To find out the differences on biomedical data between obese and non-obese participants, and to identify risk factors associated with systemic inflammation in healthy Palestinian adults. Methodology: A cross-sectional study involved 105 apparently healthy adults. Interview questionnaire was used to collect personal information. Participants were excluded if they suffered from acute or chronic inflammatory diseases, or continued using medicines, which might affect the biomedical results. Results: In association with increased Body Mass Index (BMI), the obese group displayed significant higher markers including: interleukin 6 (IL-6), high sensitivity C reactive protein (hs-CRP), total cholesterol (TC), systolic blood pressure (SBP), and diastolic blood pressure (DBP). Obese group in association with increased waist circumference (WC) was higher significantly in inflammatory markers (IL-6, hs-CRP), lipid profile (TC) and triglyceride (TG), and blood pressure (SBP, DBP). A tertile of a feature of systemic inflammation (hs-CRP) was created, by Ordinal Logistic Regression, after adjusting for the age, gender, smoking habits, physical activity pattern, father and mother's health history; risk factors were the increased BMI [OR: 1.24] (95% CI: 1.005–1.548, P = 0.050), IL-6 [OR: 3.35] (95% CI: 1.341–8.398, P = 0.010), DBP [OR: 1.19] (95% CI: 1.034–1.367, P = 0.015), and reduced Adiponectin [OR: 0.59] (95% CI: 0.435–0.820, P = 0.001). Finally, BMI correlated with IL-6 and hs-CRP ( r  = 0.326, P = 0.005; r  = 0.347, P < 0.001; respectively), and hs-CRP correlated with IL-6 ( r  = 0.303, P = 0.010), and inversely with Adiponectin ( r  = − 0.342, P = 0.001). Conclusion: The increased level of IL-6 and reduced Adiponectin, which strongly associated with obesity, indicated that having high BMI is a useful marker in association with IL-6 and further developed systemic inflammation.